Reposisi Kaidah Asbab Al-Nuzul dalam Penafsiran Al-Qur’an - Mukhlis, Febri Hijroh (Program Studi Ilmu Al-Quran dan Tafsir, 2023)
The old rule of asba>b al-nuzu>l in the interpretation of the Qur’an gives birth to textual understanding. Asba>b al-nuzu>l limits the scope of interpretation of certain verses. Because revealed verses cannot be used as the sole basis for determining the direction of interpretation of the Qur’an. This paper uses critical discourse analysis methods to assess and reconstruct the rules of asba>b al-nuzu>l contextually. In the end, asba>b al-nuzu>l was no longer considered the cause of the revelation of the verse, but rather the reason for interpreting the Qur’an. With a new position and understanding, all verses will find new reasons or causes to restore.